Densidad letal de Phyllophaga menetriesi (Coleoptera: Melolonthidae) sobre plantas de yuca (Manihot esculenta) = Lethal density of Phyllophaga menetriesi (Coleoptera: Melolonthidae) on cassava plants (Manihot esculenta) - Ortega Ojeda, CA; Melo Molina, E.L.; Gaigl, A (2007)
This experiment was designed to determine the economic damage on cassava caused by different population levels of Phyllophaga menetriesi in the Cauca Department of Colombia. The experimental units consisted of one stem cutting and four densities of the insect in third instar (one, three, five and seven grubs) confined to plastic containers with 0.028 m 3 of agricultural soil per treatment with six replications. Plant damage was evaluated using a five-level agronomic scale, ranging from an ideal plant to unrecoverable (one, three, five, seven and nine). Seventy percent of the plants survived feeding by one grub but with a 53% loss of the production potential due to consumption of the bark, medulla and roots of the stem cuttings. Three grubs per plant eliminated 50% of the experimental units in 56 days and seven in 24. Seven larvae per plant also eliminated all units in 35 days. The action threshold was determined to be less than one grub per plant and therefore planting that coincides with the root feeder should be avoided; or action should be taken when they are found on three plants for 50/ha through random sampling.